The extent to which technology has been harnessed in the teaching and learning of history at ordinary level in Gweru urban district. - Mushonga, Nancy (Midlands State University, 2017)
The purpose of this research was to investigate the extent to which technology has been harnessed in the teaching and learning of History at Ordinary level in Gweru urban District. The descriptive survey research design was used in this study. The sample constituted thirty ‘O’Level history pupils, six history teachers, three H.O.Ds and three heads of schools in Gweru urban district. The researcher used questionnaires, interviews and observations for data collection. Data was presented in form of tables and graphs followed bya discussion of the findings.Findings revealed that the integration of ICT in the teaching and learning of History at Ordinary Level was minimal and where it was employed, lots of challenges stood in its way.Lack of ICT skills by teachers and learners, interrupted power supply, high costs of computer hardware and software, lack of educational software and lack of maintenance culture were the major problems that were revealed by the research.The research recommended in servicing of teachers by the schools, development of affordable educational software by the Ministry of Primary and Secondary Education, government subsidies on ICT tools for educational purposes and also the government to ensure that teachers’ colleges were obliged to integrate ICT in all their teaching and learning processes so that they produce teachers who were not technologically averse.